Clinical and life style factors related to the nighttime blood pressure, nighttime dipping and their phenotypes in Korean hypertensive patients - Byung Sik Kim; Ju Han Kim; Wan Kim; Woo Shik Kim; Sungha Park; Sang Jae Lee; Jang Young Kim; Eun Mi Lee; Sang Hyun Ihm; Wook Bum Pyun; Jeong-Hun Shin; Jinho Shin (BMC, 2023)
Abstract Background Non-dipping or reverse dipping patterns are known to be associated with adverse cardiovascular prognosis among the general population and clinical cohort. Few large sized studies have explored factors including sleep duration and sleep quality related to nighttime blood pressure (BP) and nocturnal dipping patterns. Methods Among 5,360 patients enrolled  in Korean multicenter nationwide prospective Registry of ambulatory BP monitoring (KORABP), 981 subjects with complete data on sleep duration, sleep quality assessed using a 4-point Likert scale, and clinical variables were included in the analysis. Phenotypes of nighttime BP pattern were categorized as extreme dipper, dipper, non-dipper, and reverse dipper. Hypertension was defined as a 24-h ambulatory BPs were 130/80 mmHg or higher. Results Among 981 subjects, 221 were normotensive, 359 were untreated hypertensive, and 401 were treated hypertensive. Age of the participants were 53.87 ± 14.02 years and 47.1% were female. In overall patients, sleep duration was 431.99 ± 107.61 min, and one to four points of sleep quality were observed in 15.5%, 30.0%, 30.4%, and 24.2%, respectively. Of the 760 hypertensive patients, extreme dipper, dipper, non-dipper, and reverse dipper were observed in 58 (7.63%), 277 (36.45%), 325 (42.76%), and 100 (13.16%), respectively. In multiple linear regression analysis, sleep duration (β = 0.0105, p < 0.001) and sleep quality (β = -0.8093, p < 0.001) were associated with nighttime systolic BP and sleep quality was associated with extent of nighttime systolic BP dipping (β = 0.7622, p < 0.001) in hypertensive patients. In addition, sleep quality showed positive association with dipper pattern (odds ratio [OR] = 1.16, 95% confidence interval [CI] = 1.03-1.30) and showed negative association with reverse dipper pattern (OR = 0.73, 95% CI = 0.62-0.86) in multiple logistic regression analyses. Conclusion When adjusted covariates, less sleep duration and poor sleep quality were positively associated with nighttime systolic BP. Additionally, sleep quality was the independent associated factor for dipper and reverse dipper phenotypes. The study also found that male sex, low estimated glomerular filtration rate, high ambulatory BP, low office BP, and poor sleep quality were associated with blunted nighttime SBP dipping.